Delineation Of Seulimeum Fault System And Identification Of Geothermal Signatures Using Ground Magnetic And 2-D Resistivity Imaging Methods - Zakaria, Muhammad Taqiuddin (2017)
Ground magnetic and 2-D resistivity imaging method are widely used in geophysical exploration for subsurface identification to study the earth rheology such as fault process based on the geophysical parameter. Ground magnetic and 2-D resistivity imaging surveys were conducted to investigate the trend of Seulimeum fault system and the signature of potential geothermal surface manifestation resulting from the fault. Four different sites, namely Krueng Raya, Iejue, Lamtamot, and Tangse were chosen as study area for Seulimeum fault study while two sites; lejue and Ie-Seu 'Urn were chosen as case study areas in identifying the geothermal signatures. Ground magnetic method was performed using proton magnetometer while the 2-D resistivity imaging survey was done using ABEM Terrameter with Pole-dipole array. The magnetic residual contour map in Krueng Raya locality shows the dislocation from northwest to southeast (NW-SE) direction with contrast of high and low magnetic residual ranging from -150 nT to 300 nT which interpreted as the geological fault. In Iejue site the result shows the contrast of magnetic residual between -150 nT to 300 nT which indicate as geological fault continuous from Krueng Raya.